Ações probatórias na desconsideração da personalidade jurídica: uma perspectiva consequencialista - Zavarize, Rogerio Bellentani (2024)
Transnational companies are important for the growth of the economy and represent the fulfillment of the principle of free enterprise, guaranteed by the Federal Constitution. Their activities are regulated by the national legal system, which must ensure that they are carried out safely and predictably. The personalization of legal entities guarantees their autonomy, and their disregard is only possible, as an exception, in cases previously determined by law, and which presuppose abuse in the exercise of activities, harming third parties. The disregard of the legal personality will be sought in its own procedure, with the guarantee of an adversarial proceeding and the production of evidence relating to the assumptions that authorize disregard. This evidence can be sought through evidentiary actions, which are important tools for streamlining civil corporate proceedings, with a summary and rapid procedure. Evidentiary actions aim to secure evidence in the event of a risk of it perishing, in a precautionary role, or, in an autonomous way, to gather information about facts so that the interested parties, based on their knowledge, can decide whether to file or avoid filing a lawsuit, or lean towards enabling self-composition, especially in the context of the disregard of legal personality. Evidentiary actions for the disregard of legal personality must be dealt with from a consequentialist perspective, applying the legal system with attention and caution to the practical consequences that will result from the judicial decisions made. Consequentialism, from this perspective, requires the judge to take a careful and prudent look at the consequences in order to calibrate decisions, which must be reasoned, in order to improve the decision-making process and ensure legal certainty and predictability.